Análise do humor de trabalhadores da saúde durante a pandemia de Covid-19 - Oliveira, Leonardo Martins (2022)
The effects of the new coronavirus pandemic have affected the whole world, with inestimable loss and damage. Its consequences have even become public health problems. In this scenario, investigations on how the pandemic has affected health workers, such as stretcher bearers and security guards in public health units, are fundamental, but scarce. Thus, this study aims to investigate mental health variables of frontline healthcare workers in the covid-19 pandemic. Specifically, it aims to investigate symptoms of anxiety, depression, stress, and fear of covid-19, relating them to sociodemographic, health, and work variables. To this end, a quantitative, descriptive, cross-sectional research was conducted, in which 101 frontline health workers from four cities in Mato Grosso were individually administered the following instruments: Sociodemographic questionnaire with health and work variables, Covid-19 Fear Scale, Generalized Anxiety Disorder and Depression, Anxiety and Stress Scale-21. The results show that 50.49% of the participants are afraid of the disease between moderate and very afraid, and 68.32% have anxiety levels between mild, moderate and severe. Furthermore, 49.50% of the participants had some level of depression, 46.53% of anxious symptoms, and 56.44% of stress. Being female was associated with higher levels of generalized anxiety, anxiety, depression, stress, and fear of covid-19, losing coworkers was associated with higher levels of fear of the disease and anxiety, having sequelae of covid-19 was associated with higher levels of depression, and not having been relocated at work with higher levels of stress. It was also found that health workers in one of the cities investigated had higher levels of anxiety than those from other cities. It is discussed that psychological suffering in the context of pandemic has also significantly impacted health workers, especially females.